PEMANFAATAN MEDIA FILM DOKUMENTER DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 2 SUNGAI PANDAN - Wahyudin Noor (Universitas Lambung Mangkurat, 2015)
The purpose of this study was to determine; (1) wheter there is a difference in student’ learning outcomes in the experimental class before and after the treatment of documentary film given (pre-test-post-test), (2) Whether there is an increase (gain) of students’ learning outcomes , (3) Whether documentary film are effective media in improving students’ learning outcomes, (4) how the response of the students towards the utilization of documentary films in the teaching and learning of Social Science. This study was designed by using Pre Experimental Design of the study One Group Pre-test - Post-test. Based on the results of the study, it was found that (1) there is a significant difference in students’ learning outcomes in the experimental class before and after treatment by using documentary film given (pre-test - post-test), (2) There was an increase of (gain) of students’ learning outcomes in the experimental class after the treatment by using documentary film of 0.53 which was interpreted as moderate, (3) the effectiveness of documentary films as media to improve student learning outcomes can be seen from the increase/ difference of the pre-test and post-test result with an average of 26.48 with a deviation standard of 14.13 tasted on the media feasibility, namely judgment test where the results obtained from the test were of 73.85% from matter experts, 76.47% media expert test, 75% from computer expert so that these percentages showed that the media used in this study were feasible to be utilized (4) The students’ responses regarding the media used from the questionnaire’s total scores ranged from 36 to 44.Keywords: teaching and learning media, documentary film , learning outcomes.